The Taxation and Regulation of Banks - Keen, Michael (IMF Working Papers; Working Paper, 2011)
The financial crisis has prompted a reconsideration of the taxation of financial institutions, with practice outstripping principle: France, Germany, the United Kingdom and several other European countries have now introduced some form of bank tax, and the U.S. administration has revived its own proposal for such a charge. This paper considers the structure, appropriate rate, and revenue yield of corrective taxation of financial institutions addressed to two externalities, consequent on excessive risk-taking, prominent in the crisis: those that arise when such institutions are simply allowed to collapse, and those that arise when, to avoid the harm this would cause, their creditors are bailed out. It also asks whether corrective taxation or a regulatory capital requirement is the better way to address these concerns. The results suggest a potential role for taxing bank borrowing, perhaps as an adjunct to minimum capital requirements, at marginal rates that rise quite sharply at low capital ratios (but are likely lower when the government cannot commit to its bailout policy), reaching levels higher than those of the bank taxes so far adopted or proposed.